Experimental study of bubble departure characteristics in forced convective subcooled nucleate boiling. Issue 3 (4th May 2018) - Goel, Parul; Nayak, Arun K.; Ghosh, Pradyumna; Joshi, Jyeshtharaj B.
ABSTRACT: Visualization experiments in upward forced convective nucleate boiling flows were carried out. The bubble growth and collapse have been measured using high-speed photography technique with distilled water under atmospheric pressure. The experiments show that the bubbles depart from nucleating sites shortly after nucleation and slide along the heater surface. The bubbles grow while sliding, attain a maximum size, then lift from the surface sometime during condensation, and quickly vanish in the bulk liquid. Parametric studies show that bubble diameter and departure frequency increases with an increase in heat flux, a decrease in subcooling, and a decrease in mass flux.